The study of unit cost and quality of education of Ghazanfar Institute of Heatlh Science (GIHS) and private institutes in Kabul province from 2009 to 2012 - Ajmal Behzad (Chulalongkorn University, 2014)
Thesis (M.Sc.)--Chulalongkorn University, 2012